Copper levels in three commonly edible fruits: Are consumers at risk? - Minati Sahu; David Sylvester Kacholi (Future Science, 2021)
This study aimed to investigate levels of copper in three commonly edible fruits, namely, Lycopersicon esculenta (tomato), Citrullus lanatus (watermelon) and Cucumis sativus (cucumber) traded in Dar es Salaam city. Also, the study scrutinized risk associated with heavy metal intake in the fruits. The fruits were collected from Buguruni Market, one of the biggest markets in the city, and thereafter, were processed, and analyzed to determine copper levels. The average daily intake and human health risk indices were calculated based on the obtained copper levels. The findings revealed that the mean levels and average daily intake in L. esculenta (0.3267 mg kg-1, 0.0279 mg kg-1 person-1) and C. lanatus (0.2523 mg kg-1, 0.0216 mg kg-1 person-1) did not differ considerably (p = 0.05) from each other while the two fruits had significantly higher values than C. sativus (0.1610 mg kg-1, 0.0137 mg kg-1 person-1). The copper levels and average daily intake values were below WHO/FAO and Tanzania Bureau of Standards permissible limits. The human health index (HRI) was in the order: L. esculenta > C. lanatus > C. sativus and all the values were less than unit, suggesting that there is no health risk from consuming the fruits. Concerning copper levels, the study concludes that the fruits are safe for human consumption.